New Baxter phase in the Ashkin-Teller model on a cubic lattice - Santos, J. P.; Rosa, D. S. [UNESP]; Sa Barreto, F. C. (Elsevier B.V., 2018)
The mean field theory results are obtained from the Bogoliubov inequality for the spin-1/2 Ashkin-Teller model on a cubic lattice for different cluster sizes. The phase diagram, magnetization and free energy are obtained. From those expressions we observed a new phase in the model. Denoted in the course of this work by Baxter((2)) this new phase presents < S > not equal not equal 0. The phase transitions between the Baxter((2)) and the others well known phases for the model are studied and classified. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Ashkin-Teller model; New Baxter phase; Cubic lattice